2010
DOI: 10.1002/jhet.338
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new 2‐aryl‐4‐chloro‐3‐hydroxy‐1H‐indole‐5,7‐dicarbaldehydes via Vilsmeier‐Haack reaction

Abstract: New 2‐aryl‐4‐chloro‐3‐hydroxy‐1H‐indole‐5,7‐dicarbaldehydes were synthesized in three steps from acetophenone derivatives. By oxidation of acetophenones to aryl glyoxals using selenium dioxide and condensation with acetylacetone in the presence of ammonium acetate in water 3‐acetyl‐5‐aryl‐4‐hydroxy‐2‐methyl‐1H‐pyrrols were obtained. 2‐Aryl‐4‐chloro‐3‐hydroxy‐1H‐indole‐5,7‐dicarbaldehydes were synthesized via Vilsmeier‐Haack reaction of pyrrole derivatives in moderate yields. J. Heterocyclic Chem., (2010).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…The proposed mechanism involves a series of interconnected reactions, starting from the addition of (23) to iminium salt (1), progressing through iminoalkylation and cyclization of bis-iminium salt (24) to enamine (25), followed by the elimination of dimethylamine. The resulting bis-iminium salt (26) undergoes hydrolysis, culminating in the synthesis of 2-aryl-4-chloro-3-hydroxy-1 H -indole-5,7-dicarbaldehydes (27) as the final product 93 ( Scheme 57 ).…”
Section: Synthesis Of Fused-rings Heterocyclic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed mechanism involves a series of interconnected reactions, starting from the addition of (23) to iminium salt (1), progressing through iminoalkylation and cyclization of bis-iminium salt (24) to enamine (25), followed by the elimination of dimethylamine. The resulting bis-iminium salt (26) undergoes hydrolysis, culminating in the synthesis of 2-aryl-4-chloro-3-hydroxy-1 H -indole-5,7-dicarbaldehydes (27) as the final product 93 ( Scheme 57 ).…”
Section: Synthesis Of Fused-rings Heterocyclic Compoundsmentioning
confidence: 99%
“…In 2010, Eftekhari et al 93 reported 2-aryl-4-chloro-3-hydroxy-1 H -indole-5,7-dicarbaldehydes from 3-acetyl-5-aryl-4-hydroxy-2-methyl-1 H -pyrroles using V. H. reagent in cold condition for 1 hour followed by stirring the reaction mixture at 55 °C for 2 hours and further stirred overnight at room temperature in average yield. The resulted products were expected to display a wide range of biological activities ( Scheme 58 ).…”
Section: Synthesis Of Fused-rings Heterocyclic Compoundsmentioning
confidence: 99%